The Ideological Ranting in the Debut Novels of the Contemporary Pakistani Writers - Nadeem, Mariam; Saeed, Sohail Ahmad (Pakistan Journal of Humanities and Social Sciences, 2021)
People believe that ideologies work for their betterment by showing them a path of prosperity. However, they fail to understand the consequences of blindly following a specific ideology. In their debut novels, the contemporary writers of Pakistan depict the working of one of these ideologies: religion. The present study aims to analyze the projection and exploitation of power in the name of religion: how people suffer for the sake of faith, and the manipulation that follows it in these selected novels: The Prisoner, A Case of Exploding Mangoes, How it Happened, and Agency Rules. The study also highlights the link between religious ideology and the conditioning of the minds of people. The analysis takes place in the light of Marxist theory. The study discovers the role of religious ideology in overpowering helpless people with the belief that following a certain path will reward them in life after death.